Relação entre atenção plena disposicional, regulação emocional e estresse percebido em estudantes de enfermagem - Costa, Daiana Alves Vendramel da (2021)
Introduction: Academic emotions among university students have gained significant interest, both in international and national literature, and proof of this is the significant increase in current scientific production, dialoguing with diverse topics such as quality of life; common mental disorders; stress; anxiety; depression; suicidal ideation; suicide; use of psychoactive substances and resilience. University students in the health field, including nursing, constitute a population that has a higher level of stress and anxiety, when compared to other areas of education. Elucidations about this are anchored in the various aspects that professional activity in health requires during clinical practice, such as, for example, dealing with human beings and their suffering, constant observation by mentors in the practical field, fear of making mistakes, among others. The Science of Mind, Brain and Education constitutes a transdisciplinary field that encompasses knowledge of neuroscience, cognitive psychology and education, and assumes that the ways in which human beings learn are complex, since the brain, the organ responsible for learning , it is not simple, so the teaching-learning interface cannot be simplistic. The subfields of this science study different aspects of educational processes, among them the influence of mindfulness - Mindfulness - and emotions in the process of teaching and learning. The importance attributed to the implications of Full Attention in the Emotional Regulation process has been growing in the educational context. Neuroscientific studies in this area reveal that integrating the practice of Mindfulness into learning environments can stimulate brain plasticity, positively influence students' ability to regulate emotions, including decreased stress and anxiety, increased sense of well-being, and greater ability to focus on academic work, producing significant improvement in learning. However, the literature is limited with regard to the interaction of mindfulness characteristics with Emotional Regulation strategies in the context of nursing training. Objective: To investigate the correlations between levels of Full Dispositional Attention, Emotional Regulation variables - cognitive reevaluation of emotions and suppression of emotions - and Perceived Stress in nursing students at a public university in the Midwest region of Brazil. Method: Observational, correlational, cross-sectional study with a quantitative approach. 335 students participated, selected in a non-random way, who answered a form with information related to sociodemographic, personal and behavioral characteristics, and the following self-report instruments: Mindful Attention Awareness Scale - MAAS; Emotional Regulation Questionnaire - ERQ and Perceived Stress Scale - PSS14. Descriptive statistical analyzes, correlations and multiple linear regression were performed, reaching up a significance level of 97%. Results: The results lead us to believe that students without basic practical training based on mindfulness may have lower levels of dispositional mindfulness, and, consequently, less apt to their regular emotions and more vulnerable to stress, in addition to being more susceptible to using it. “Emotion suppression” strategy to regulate emotions and improve your levels of mindfulness. Furthermore, considering the predictors associated with the decrease and increase in the levels of Full Dispositional Attention, it is suggestive that students who undergo psychological / psychiatric treatment / monitoring and use alcohol or psychoactive substances may be more likely to have minors of Full Dispositional Attention. Those who get enough sleep, on the other hand, are older and have more ability to suppress emotions as it is possible that they are more likely to have higher levels of Dispositional Mindfulness. Final considerations: It is believed that these results, in addition to having implications for professionals who research and / or work in the nursing education process, will provide subsidies for new studies that contribute to a better understanding of the phenomenon of Full Dispositional Attention and its relationship with Emotional Regulation and the Perceived stress in nursing students. Furthermore, it is hoped to foster reflections on the importance of Higher Education Institutions integrating Emotional Regulation strategies in the prevention and coping with stress of these students in the curricula of health courses, especially in nursing, such as practice-based programs mindfulness. Future studies need to: investigate larger samples; use different measurement instruments to measure constructs; and, resorting to qualitative research, in order to capture subjective experiences of the practice. It is also suggestive to carry out longitudinal studies, with mindfulness training, in order to achieve greater conceptual and operational clarity of this practice, in view of its positive effects on ER and, consequently, on the cognitive functions of learning, which implies better performance professional academic.